Tekst główny a tekst zależny. O wariacjach tworzenia fandomów i narracji transmedialnych wokół twórczości autorki-fanki - Żubryk, Klaudia (Załącznik Kulturoznawczy, 2024)
The presence of popular culture fans has become all the more visible in the public space. Fandoms function by to their own rules, producing, to quote John Fiske, in three models: semiotic, textual and enunciative activity. Each of the activities that fit into the model is characterized by a distinct creative strategy – and the similar applies to fan fiction. This article is a case study dedicated to the works of one of the most popular authors of Polish fan fiction, ChoJulieSsie: the writing strategies, the reception practices of the work, and finally, the stimulation of the emergence of an engaged community and a distinct story breaking away from the original text. In the process of analysis, I use the categories of fan productivity and transmedia narrative to trace the way their community was formed. The main aim of this article is to outline the phenomenon of the emergence of a new fandom from an earlier one, being an extension and at the same time (in-)formation of a new transmedia narrative and the consequences of such practices.